Morphological Identification of Oudemansiella canarii (Jungh.) Höhn. at IPB University Campus Forest - Litta Zulvawati Ardi; Nuzrina Ardhani; Risya Ayudya Fadillah; Chelsea Dame Natalia; Indah Tasya Nabila; Made Jefry Dwi Dharma; Ivan Permana Putra (JURNAL SAINS NATURAL, 2023)
Oudemansiella canarii is a wild mushroom which easy to find in nature and usually grows on wood. This mushroom is recognized as the edible macrofungi, but information on the morphological characteristics of this fungus is very limited in Indonesia. Therefore, this study aimed to identify and describe O. canarii based on morphological features as an effort to disseminate mycology information to the public. This research was conducted in the IPB University campus forest which is one of the natural habitats of this macrofungi. The fruiting bodies were observed in the field and in the laboratory. Identification was carried out based on the macroscopic and microscopic characteristics of the collected specimens. Oudemansiella canarii observed had a cream-colored cap, scales on its surface, a cap covered with mucus, free lamellae attachments, club-shaped basidia, basidiospores globose to subglobose, hyaline with thin walls, without ornamentation, and has a clearly visible guttule. This report is the first comprehensive morphological description on O. canarii from Indonesia and adds information to the diversity of Indonesian macrofungi.